Analisis Pelanggaran Hak Konsumen terhadap Kasus Pengoplosan Beras Merek Daun Suji - Elvira Clarista Faiqah; Rodhia Tammardhiah; Qian Ramadhani; Vincent Anderson Simanjuntak (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Consumer protection in Indonesia is regulated in Law No. 8/1999 on Consumer Protection (UUPK), which emphasizes consumers' basic rights to safe and quality goods. This research focuses on the violation of consumer rights in the “Daun Suji” brand rice oplosan case, which came to light in February 2025. The results show that the oplosan “Daun Suji” rice does not meet the promised premium rice quality standards. This resulted in a violation of consumer rights, specifically Article 4 letters b and c of the Consumer Protection Law. These violations include the right of consumers to choose goods according to exchange value and guarantees, as well as the right to correct and clear information. This fraudulent practice harms consumers who expect quality products at the price paid.